Prenatal Diagnosis of Omphalocele and Soft Markers of Chromosomal Abnormalities In The First Trimester - Rina Gustuti (Journal of Midwifery, 2025)
Physiological herniation of the fetal midgut into the umbilical cord occurs during early embryonic development as a result of limited intra-abdominal space and is considered a normal finding until approximately 10-11 weeks of gestation. Persistence of midgut herniation beyond 12 weeks of gestation, or the presence of a herniated mass with a diameter exceeding 7 mm, is regarded as pathological and consistent with a diagnosis of omphalocele. Early identification during the first trimester is of substantial clinical importance, as omphalocele is frequently associated with chromosomal abnormalities, particularly trisomy 18, trisomy 13, and trisomy 21. In this setting, healthcare providers especially midwives working in close collaboration with fetomaternal specialists play a pivotal role in early screening, timely referral, and provision of psychosocial support. We report the case of a 22-year-old woman, gravida 2 para 1 abortus 0 living 1 (G2P1A0H1), at 11 weeks of gestation, who presented with hyperemesis gravidarum complicated by mild to moderate dehydration and reduced oral intake. Fetomaternal ultrasonography demonstrated a single live intrauterine fetus consistent with gestational age, with a crown– rump length of 39.4 mm (15.3rd percentile) and a regular fetal heart rate of 164 beats per minute. Notable findings included a markedly increased nuchal translucency of 6.8 mm, visualization of the nasal bone, normal ductus venosus Doppler flow, and a 9-mm membranous herniation at the umbilical cord insertion, consistent with omphalocele. In conclusion, first-trimester ultrasonography enabled early prenatal diagnosis of omphalocele accompanied by chromosomal soft markers. Further management includes cytogenetic analysis and a detailed second- trimester anatomical assessment, supported by comprehensive counseling to facilitate informed clinical decision-making.